2021
DOI: 10.1002/ptr.7084
|View full text |Cite
|
Sign up to set email alerts
|

Phyto‐pharmacological perspective of Silymarin: A potential prophylactic or therapeutic agent for COVID‐19, based on its promising immunomodulatory, anti‐coagulant and anti‐viral property

Abstract: Coronavirus disease 2019 (COVID‐19) triggered by a new viral pathogen, named severe acute respiratory syndrome Coronavirus‐2 (SARS‐CoV‐2), is now a global health emergency. This debilitating viral pandemic not only paralyzed the normal daily life of the global community but also spread rapidly via global travel. To date there are no effective vaccines or specific treatments against this highly contagious virus; therefore, there is an urgent need to advocate novel prophylactic or therapeutic interventions for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 90 publications
(108 reference statements)
0
20
1
Order By: Relevance
“…Because of multisystemic disease COVID‐19, many studies have been published confirming the anti‐SARS‐CoV‐19 effect of flavonoids (Palit, Mukhopadhyay, & Chattopadhyay, 2021 ; Santana et al, 2021 ).…”
Section: Flavonoidsmentioning
confidence: 99%
“…Because of multisystemic disease COVID‐19, many studies have been published confirming the anti‐SARS‐CoV‐19 effect of flavonoids (Palit, Mukhopadhyay, & Chattopadhyay, 2021 ; Santana et al, 2021 ).…”
Section: Flavonoidsmentioning
confidence: 99%
“…Emerging data suggest polyphenols as potential immunomodulatory and/or antiviral agents against COVID‐19. The present virtual issue contains review addressing the potential of flavonoids, curcumin, resveratrol and silibinin in attenuating lung injury and cytokine storm associated with the disease (Derosa et al, 2021 ; Di Petrillo, Orrù, Fais, & Fantini, 2021 ; El‐Missiry, Fekri, Kesar, & Othman, 2021 ; Gour, Manhas, Bag, Gorain, & Nandi, 2021 ; Khezri, Saeedi, Mohammadamini, & Zakaryaei, 2021 ; Palit, Mukhopadhyay, & Chattopadhyay, 2021 ; Pawar & Pal, 2020 ; Santana et al, 2021 ). Studies on specific polyphenols showed that (a) kaempferol inhibited the SARS‐CoV‐2 main protease (3CLpro) (Khan et al, 2021 ), (b) oroxylin suppressed the entrance of the SARS‐CoV‐2‐spiked pseudotyped virus into ACE2 cells (Gao et al, 2021 ), (c) resveratrol inhibited the replication of SARS‐CoV‐2 in cultured Vero cells (M. Yang et al, 2021 ) and (d) silibinin interacted with SARS‐CoV‐2 main target proteins (e.g., spike protein RBD and Mpro residues) (Speciale et al, 2021 ).…”
Section: Polyphenolsmentioning
confidence: 99%
“…Finally, other review articles highlighted traditional herbs or phytochemicals for the management of cardiovascular sign and symptoms(Mohammadi Pour, Farzaei, Soleiman Dehkordi, Bishayee, & Asgary, 2021) or to overcome stress, anxiety and improve mental health associated with COVID-19(Shahrajabian, Sun, Soleymani, & Cheng, 2021).3 | POLYPHENOLSEmerging data suggest polyphenols as potential immunomodulatory and/or antiviral agents against COVID-19. The present virtual issue contains review addressing the potential of flavonoids, curcumin, resveratrol and silibinin in attenuating lung injury and cytokine storm associated with the disease(Derosa et al, 2021;Di Petrillo, Orrù, Fais, & Fantini, 2021;El-Missiry, Fekri, Kesar, & Othman, 2021;Gour, Manhas, Bag, Gorain, & Nandi, 2021;Khezri, Saeedi, Mohammadamini, & Zakaryaei, 2021;Palit, Mukhopadhyay, & Chattopadhyay, 2021;Pawar & Pal, 2020;Santana et al, 2021).…”
mentioning
confidence: 99%
“…In addition, glutathione, glutathione peroxidase, superoxide dismutase, and catalase activities were significantly lower among the COVID-19 patients than in the control group. 132 Literature reviews suggested that some antioxidant like melatonin, 133 zinc, 134 vitamin C, 135 glutathione, 136 L-carnitine, 137 honey, 138 selenium, 130 silymarin, 139 astaxanthin, 140 quercetin, 141 and pentoxifylline 142 may provide beneficial and supportive treatments against COVID-19 infection by anti-apoptotic, anti-viral, and anti-inflammatory properties.…”
Section: Antioxidantsmentioning
confidence: 99%